Utility of Angioembolization in Patients with Abdominal and Pelvic Traumatic Bleeding: Descriptive Observational Analysis from a Level 1 Trauma Center - Al-Thani H (Dove Medical Press, 2021)
Hassan Al-Thani,1 Husham Abdelrahman,2 Ali Barah,3 Mohammad Asim,4 Ayman El-Menyar4,5 1Department of Surgery, Trauma&Vascular Surgery, Hamad General Hospital, Doha, Qatar; 2Department of Surgery, Trauma Surgery, Hamad General Hospital, Doha, Qatar; 3Department of Radiology, Hamad General Hospital, Doha, Qatar; 4Department of Surgery, Clinical Research, Trauma & Vascular Surgery, Hamad General Hospital, Doha, Qatar; 5Department of Clinical Medicine, Weill Cornell Medical School, Doha, QatarCorrespondence: Ayman El-MenyarClinical Research, Trauma &vascular Surgery, Hamad General Hospital, Doha, QatarTel +974 44394029Email aymanco65@yahoo.comBackground: Massive bleeding is a major preventable cause of early death in trauma. It often requires surgical and/or endovascular intervention. We aimed to describe the utilization of angioembolization in patients with abdominal and pelvic traumatic bleeding at a level 1 trauma center.Methods: We conducted a retrospective analysis for all trauma patients who underwent angioembolization post-traumatic bleeding between January 2012 and April 2018. Patients’ data and details of injuries, angiography procedures and outcomes were extracted from the Qatar national trauma registry.Results: A total of 175 trauma patients underwent angioembolization during the study period (103 for solid organ injury, 51 for pelvic injury and 21 for other injuries). The majority were young males. The main cause of injury was blunt trauma in 95.4% of the patients. The most common indication of angioembolization was evident active bleeding on the initial CT scan (contrast pool or blushes). Blood transfusion was needed in two-third of patients. The hepatic injury cases had higher ISS, higher shock index and more blood transfusion. Absorbable particles (Gelfoam) were the most commonly used embolic material. The overall technical and clinical success rate was 93.7% and 95%, respectively, with low rebleeding and complication rates. The hospital and ICU length of stay were 13 and 6 days, respectively. The median injury to intervention time was 320 min while hospital arrival to intervention time was 274 min. The median follow-up time was 215 days. The overall cohort mortality was 15%.Conclusion: Angioembolization is an effective intervention to stop bleeding and support nonoperative management for both solid organ injuries and pelvic trauma. It has a high success rate with a careful selection and proper implementation.Keywords: angioembolization, trauma, injury, bleeding, pelvic, solid organ